Understanding the influence of antipsychotic drugs on global methylation events and its relevance in treatment response. (March 2018) - Swathy, Babu; Saradalekshmi, Koramannil R; Nair, Indu V; Nair, Chandrasekharan; Banerjee, Moinak
Aim: The present study intends to evaluate whether antipsychotic drugs can modulate the host epigenome and if so whether drug-induced epigenetic modulation can explain the heterogeneity in drug response.Methods: Present study was conducted in in vitro cells and significance of these in vitro observations was further evaluated in a clinical setting, between drug responsive and nonresponsive schizophrenia patients. A number of DNA modifications were assessed at global level using 5-methylcytosine, 5-hydroxymethylcytosine and 5-formylcytosine followed by evaluating the expression of epigenetic modifier genes and their crosstalk with miRNAs.Results: In vitro data demonstrated that antipsychotic drugs induce epigenetic response by downregulating miRNA that target DNA methyltransferases, resulting in global hypermethylation. Similar trend was observed in clinical setting too and alterations were markedly associated with drug response rather than disease pathogenesis.Conclusion: Study demonstrates that antipsychotic drugs can influence host methylome and thereby indicating its role in mediating a strong pharmacoepigenomic response.